2020
DOI: 10.1080/00224499.2020.1784827
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Satisfaction and Sexual Identity

Abstract: This study addressed three goals related to better understanding the factors that contribute to female sexual satisfaction: (a) exploring differences in factors that contribute to perceptions of sexual satisfaction among women with varying sexual identities, (b) evaluating an existing measure of sexual satisfaction among women with diverse sexual identities, and (c) developing potential items for a future expanded measure of the factors contributing to sexual satisfaction.Participants were 996 heterosexual wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…Holt et al [48] report that several important differences in factors related to sexual satisfaction also occur as a function of sexual identity. Although the present study assessed dyspareunia in participants whose sexual function could encompass both opposite-sex and same-sex sexual interactions, a complete sexual function assessment can and should include much more.…”
Section: Issues Beyond the Endometriotic Lesionsmentioning
confidence: 99%
“…Holt et al [48] report that several important differences in factors related to sexual satisfaction also occur as a function of sexual identity. Although the present study assessed dyspareunia in participants whose sexual function could encompass both opposite-sex and same-sex sexual interactions, a complete sexual function assessment can and should include much more.…”
Section: Issues Beyond the Endometriotic Lesionsmentioning
confidence: 99%
“…Have 10.31580/jrp.v4i2.2564 sexual satisfaction, marital compatibility and excellent emotional relationship, and people with negative sexual self-concept control romantic sex and report more sexual problems (Guyon R et al, 2020;Nik et al, 2018). In a study, it was observed that homosexual women report less sexual satisfaction and marital compatibility than heterosexual women (Holt, Chung, Janssen, & Peterson, 2021). Significant sexual events influence the positive and negative elements of general sexual self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have revealed little or no differences in sexual satisfaction when comparing lesbian and heterosexual women (Kuyper & Vanwesenbeeck, 2011;Matthews et al, 2003). On the other hand, according to Holt et al (2021), several of the factors that contributed to the sexual satisfaction of bisexual women were different from those that contributed to the satisfaction of heterosexual and lesbian women. The authors concluded that the findings from their study demonstrate the importance of considering sexual identity in relation to sexual satisfaction and when providing interventions to improve sexual satisfaction.…”
Section: Sexual Satisfactionmentioning
confidence: 99%